Penanganan Kasus Kekerasan Seksual Terhadap Anak - Ambodo, Triyo; Rochim, Fathur (Bahasa Indonesia, 2024)
The evaluation of handling sexual violence cases against children in Indonesia shows that although policies and regulations have been formulated, their implementation still faces various challenges. This study aims to evaluate the effectiveness of child protection policies, including Law No. 35 of 2014 and Law No. 12 of 2022 concerning Sexual Violence Crimes (TPKS). The research method used is a qualitative approach with data collection through interviews, observations, and documentation studies. The results indicate that successes in handling cases of sexual violence against children are reflected in the increasing public awareness to report and the improved support services for victims. However, many obstacles remain, such as limited human resources, social stigma, and a lack of coordination among agencies. Recommendations for improvement include strengthening inter-agency coordination, training for professionals, and community awareness campaigns to prevent and report cases of sexual violence.